Fallen tree problems in the field of landscape architecture in Malaysia / Ahmad Zamil Zakaria - Zakaria, Ahmad Zamil (2012)
A study of fallen trees and their impact on the field of landscape architecture is carried out based on media reports in Malaysia. This incident is very worrying fallen tree population in this country, whether located in urban areas or rural areas. The public now want the best solution to reduce the threat of fallen trees that may occur unexpectedly. The situation experienced by Malaysians today is likely due to the lack of concern in the choice of appropriate plant species and a lack of maintenance knowledge. Threats of fallen tree also happen if the correct method is not practiced and not in accordance with planting guidelines that have been provided. Many of us are involved in the maintenance of landscape areas such as urban forests, recreation, maintenance of roads and private residences. All these require of expert advice and professional opinion to identify the needs in managing trees, which if neglected appear to be dangerous to the public. Today, the issue of safe tree planting should be practiced in order to prevent incidents of fallen trees in future. A complete and proper documentation must be implemented so that it there will be accurate and reliable reference to address the issues of this predicament.